2008
DOI: 10.1614/wt-07-128.1
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and Control of Glyphosate-Resistant Palmer Amaranth (Amaranthus palmeri) in Arkansas

Abstract: Failure of glyphosate to control Palmer amaranth was first reported in Arkansas in Mississippi County in June, 2005. The objectives of this research were to (a) confirm glyphosate-resistant Palmer amaranth in Arkansas, and (b) determine the effectiveness of 15 postemergence- (POST) applied herbicides comprising eight modes of action in controlling the glyphosate-resistant biotype compared to glyphosate-susceptible accessions. The LD50 values were similar among three susceptible Palmer amaranth accessions, rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
209
4
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(223 citation statements)
references
References 14 publications
6
209
4
4
Order By: Relevance
“…On the basis of ED 90 values, the GR biotype had a 37-to 40-fold level of resistance depending on the susceptible biotype being used for comparison (Table 3). Culpepper et al (2006) reported 50% control of a GR Palmer amaranth biotype from Georgia with glyphosate applied at 1,200 g ha -1 , and Norsworthy et al (2008) reported 50% control of a GR Palmer amaranth biotype from Arkansas with glyphosate applied at 2,820 g ha −1 , 1.57-fold higher application rate than that observed in this study (1,787 g ha −1 ). Dose-response curves for GR Palmer amaranth biomass reduction indicated similar levels of resistance (35-to 36-fold) indicated by ED 90 values based on visual control scores ( Figure 2, Table 4).…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…On the basis of ED 90 values, the GR biotype had a 37-to 40-fold level of resistance depending on the susceptible biotype being used for comparison (Table 3). Culpepper et al (2006) reported 50% control of a GR Palmer amaranth biotype from Georgia with glyphosate applied at 1,200 g ha -1 , and Norsworthy et al (2008) reported 50% control of a GR Palmer amaranth biotype from Arkansas with glyphosate applied at 2,820 g ha −1 , 1.57-fold higher application rate than that observed in this study (1,787 g ha −1 ). Dose-response curves for GR Palmer amaranth biomass reduction indicated similar levels of resistance (35-to 36-fold) indicated by ED 90 values based on visual control scores ( Figure 2, Table 4).…”
Section: Resultscontrasting
confidence: 45%
“…Jhala et al (2014) have further reported 83% to 97% control of three Palmer amaranth biotypes with dicamba or 2,4-D ester applied at 560 g ae ha -1 . Similarly, Norsworthy et al (2008) reported >95% control of GR palmer amaranth with dicamba and 2,4-D amine applied alone at 280 and 560 g ha -1 , respectively; however, the reduced control (74%) of GR Palmer amaranth with 2,4-D ester in this study might be due to the use of the lowest labelrecommended rate (386 g ha -1 ).…”
Section: Palmer Amaranth Biotypescontrasting
confidence: 55%
See 1 more Smart Citation
“…A. palmeri is dioecious (4) and is an economically troublesome weed threatening the sustainability of cotton production in the southeastern United States (5), where glyphosate has been the principal tool for A. palmeri control since 1997. Unfortunately, glyphosate resistance has now evolved in A. palmeri populations within glyphosate-resistant cotton fields reported in Georgia (3), Tennessee (6), North Carolina (7), South Carolina (8), and Arkansas (9). In 2009, glyphosate-resistant A. palmeri was projected to occur on at least 250,000 ha of crop land (8).…”
mentioning
confidence: 99%
“…A Palmer amaranth inflorescence from each of four female plants was collected from 21 fields in three counties in northeastern Arkansas in October and November of 2006 (Table 1). Accession AR1 was the site from which Palmer amaranth seeds had been collected from the soil seedbank the previous year and later confirmed to be resistant to glyphosate (Norsworthy et al 2008a). Sites were chosen solely on the presence of Palmer amaranth prior to crop harvest rather than previous failure of glyphosate to control the weed.…”
Section: Methodsmentioning
confidence: 99%